Analysis of the Readiness of the Apron Movement Control Unit in the Embarkation and Debarkation Phases of Hajj Flights in 2022 at Adi Soemarmo Boyolali International Airport - Franzeska Windy Ayu Chabelita; Nur Makkie Perdana Kusuma (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
In the service of flight activities on the air side, it requires the role and supervision and regulation of air traffic from the Apron Movement Control (AMC) unit. Adi Soemarmo International Airport is one of the hajj embarkation airports in Indonesia, especially in Central Java and Yogyakarta. When there are Hajj flight activities, the airport operation hour will be 24 hours while still dividing work time. In handling haj flights, the AMC unit oversees the movement of haj transport buses from or to planes so that researchers aim to analyze the readiness of the AMC unit in the embarkation and debarkation phases of hajj flights at Adi Soemarmo International Airport in 2022.This research is descriptive using qualitative methods with data collection methods in the form of interviews and documentation. The data obtained were in the form of observations, interviews with AMC unit personnel at Adi Soemarmo International Airport as well as documents used to carry out the pilgrimage activities.The results of this study indicate that from secondary data that analyzes AMC unit documents are follow me car services, aircraft parking placements, special terminals for Hajj flights and Hajj flight schedules, based on standard operation procedure (SOP) data, namely follow me car services placing aircraft parking . hajj flight special terminal and haj flight schedule. The results of the interview with AMC at Adi Soemarmo International Airport will increase the number of human resources due to the division of work time due to the lack of AMC unit workers. During the hajj flights, the operation of Adi Soemarmo International Airport became 24 hours, the airport operating hours changed from 07.00 WIB to 20.00 WIB/last night to 24 hours with the number of AMC unit personnel only 2 to 3 people per shift, both regular flights and during flights pilgrimage. However, this is not a workload for the AMC unit in dealing with haj flights.